A critical success factors for software project manager in GVTs within covid-19 pandemic - Ali Yahya Gheni; Hiba Adil Yousif; Yusmadi Yah Jusoh (Institute of Advanced Engineering and Science, 2021)
The covid-19 pandemic sweeping the world and has rendered a large proportion of the workforce as they are unable to commute to work. This has resulted in employees and employers seeking alternative work arrangements, including the software industry. Then comes the need for the global market and international presence of many companies to implement the global virtual teams (GVTs). GVTs members are gradually engaged in globalized business environments across space, time and organizational boundaries via information and communication technologies. Despite the advancement of technology, the project managers are still facing many challenges in communication. Hense, to become a successful project manager still a big challenge for them. This study is trying to identify the critical success factors (CSFs) for software project manager. A literature review was conducted to identify the CSFs. Next, an online survry was conducted to rank those factors according to their propriety. An online survey was distributed among the software developers, project managers, and academicans. The statistical package for social science (SPSS) version 22 was used to analyze the data collection. Twelfth CSFs were identified in this study. Also, the findings indicated that leadership skills factor is the highest factor level ranking in this study.